(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
In this essay I seek to discuss possible points of contact between theories and models of the State and of analysis of public policies in the field of Political Science, and a behaviorist conception of human behavior at the field of Psychology. Therefore, at first the behaviorist conception of behavior and the concept of controlling agency are presented, the latter seem as directly related to the former in the effort to understand societal and institutional dimensions of behavior; this goes as an effort to understand its possible relations with theoretical models of the State. Then, starting from basic literature on the field of Political Science are presented some of the main theoretical models of analysis of public policies. Lastly, convergences and divergencies typical of multidisciplinar efforts like this are highlighted, in the search for dialogue pathways between different fields interested in politics, policies and the behavior of political actors.